Determinants of the adoption of mobile phones for fruit marketing by Vietnamese farmers. (March 2020) - Hoang, Hung Gia
Highlights: Farmers used mobile phones as the key ICT tool to seek market information. Male farmers are in a better position to use mobile phones than female farmers. Farmers who live far from local markets tend to be ICT users. Farmers who participated in training programs are better ICT users than those who did not take part in them. High costs and lack of knowledge/skills hindered farmers to adopt ICT tools. Abstract: Making farmers more informed about information and market opportunities is generally considered a significant way to improve their livelihood. Information Communication and Technologies (ICTs) can be important means of doing that. In order to facilitate farmers' adoption of ICTs for agricultural produce marketing, it is critical to understand factors that affect its adoption. However, few empirical studies have considered determinants of farmers' adoption of ICTs for marketing in Vietnam. This research investigates factors that shape adoption of ICT tools (mobile phones) for fruit marketing in Huong Son district, Vietnam. A random sample of 180 was drawn from a total of 325 farmers. Descriptive statistics, inferential statistics and a binary logistic regression were applied to analyse the data. The study concluded that young male farmers living far from local markets, who have high incomes and participate in training programs, have a greater tendency to adopt ICT tools (mobile phones) for fruit marketing. Demographic, socio-economic, situational and institutional characteristics of farmers should be considered when promoting farmers' adoption of ICT tools for agricultural produce marketing and when selecting marketing information strategies to deliver to small-scale farmers in developing countries.